2013
DOI: 10.5430/jha.v3n2p24
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of physical disorder in children with mental disorder: A health care utilization study

Abstract: Objective: This study examines, across physician billing, ambulatory and inpatient/emergency datasets, the health care utilization of individuals under the age of 18 years for physical disorders in relationship to the existence of a physician assigned psychiatric disorder. Methods:A retrospective sample of all visit records from three datasets (physician billing, ambulatory records, and inpatient/emergency records n = 12687710) was constructed for cases (n = 26392) and comparisons (n = 205281). The mean number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…To date, research has identified a relationship between ACE survey total score and clinical urgency and severity. 1 In keeping with results from the original population-based ACE study, 2 regional findings have shown a relationship between physical disorders and mental disorder as a potential endpoint for early adverse experience in children, adolescents, and adults, 1,3,4 in addition to the relationship of mental disorder with chronic and preventable disease. 5,6 As formulating psychiatric diagnoses is a cornerstone of practice, it stands to reason that an examination of its relationship to individual ACE items is warranted.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…To date, research has identified a relationship between ACE survey total score and clinical urgency and severity. 1 In keeping with results from the original population-based ACE study, 2 regional findings have shown a relationship between physical disorders and mental disorder as a potential endpoint for early adverse experience in children, adolescents, and adults, 1,3,4 in addition to the relationship of mental disorder with chronic and preventable disease. 5,6 As formulating psychiatric diagnoses is a cornerstone of practice, it stands to reason that an examination of its relationship to individual ACE items is warranted.…”
Section: Introductionmentioning
confidence: 69%
“…Of note is that the first group representing the collapsed data maximizes the number of diagnoses for each individual in the ACE score distribution, whereas the multiple-admissions dataset maximizes the number of diagnoses over admissions for each individual in the ACE score distribution. The collapsed and multiple-admissions datasets are presented in tandem throughout Tables [1][2][3][4][5][6] and are also identified in relation to the sample sizes in each. Note in Table 1 that the 2 distributions for each group (males and females) are representative of one another for values greater than 0, with the greatest difference being under 5% in Value 1 items for males and females.…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, the necessity for CYMH services exceeds the existing capacity. [9] The current situation calls attention to making CYMH a social priority by enhancing current services to address issues, such as improved coordination of care, [24] developing new initiatives to overcome barriers to service, such as mental health stigma, [25] and implementing strategies to reduce wait times to create needed access to service for young people and families affected by mental disorders and mental health difficulties. [26] 1.2 Overview of the Western Canada Waiting List (WCWL) project…”
Section: Introductionmentioning
confidence: 99%